Analisis Kualitas Air Dari Pegunungan Lapole Untuk Suplai Air Bersih Bagi Penduduk - Elfi Yuliana; La Harudu; Sitti Kasmiati (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
The springs in Lapole Village are one of the most potential sources of water for residents in Lapole Village for domestic needs. Over the years, people have used this water source by consuming it directly, but along with the increase in population, the need for clean water has also increased. The purpose of this study was to analyze the condition of the quality of drinking water directly from the springs of Mount Lapole in terms of physical parameters, chemical parameters and biological parameters. In this study, samples were taken from one point in the spring and one point in the settlement. Furthermore, the parameters of smell, taste, color and temperature were tested visually while the parameters of TDS, pH and DO as well as MPN coliform and E. Coli testing were carried out in the laboratory. The results showed that based on the results of direct sample examination and through the laboratory, Mount Lapole water met the physical, chemical and biological requirements with the following details: 1) physical parameters, namely odorless, tasteless, colorless and an average temperature of 23°C and 25°C, and total dissolved solid (TDS) at station 1 averaged 83,288 (mg/l) and station 2 averaged 85,994 (mg/l); 2) chemical parameters, i.e. pH test at station 1 averaged 7.91 and station 2 averaged 8.01, dissolved oxygen (DO) test at station 1 had DO 6.048 (mg/l) and station 2 averaged -average 6.023 (mg/l); and 3) biological parameters, namely the result of the MPN/100 ml coliform test was 15 and the number of E. Coli was 0. Based on these results, it can be concluded that Mount Lapole water is fit for consumption in the long term.